2015
DOI: 10.4049/jimmunol.1402217
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Augmented Efferocytosis Inhibits Pulmonary Pneumococcal Clearance in Mice by Reducing Alveolar Macrophage Bactericidal Function

Abstract: Inhaled corticosteroid(s) (ICS) increase community-acquired pneumonia (CAP) incidence in patients with chronic obstructive pulmonary disease (COPD) by unknown mechanisms. Apoptosis is increased in the lungs of COPD patients. Uptake of apoptotic cells (AC) (“efferocytosis”) by alveolar macrophages (AMø) reduces their ability to combat microbes, including Streptococcus pneumoniae, the most common cause of CAP in COPD patients. Having shown that ICS significantly increase AMø efferocytosis, we hypothesized that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 104 publications
0
36
0
Order By: Relevance
“…Furthermore, removal of dead/dying cells by AMs results in subsequent impaired phagocytosis and bacterial killing and impaired clearance of S. pneumoniae. 24 Moreover, it has been shown that administration of glucocorticoids during active murine pneumonia infection further hinders the ability of AMs to kill bacteria via inhibition of cytokine production 25. This highlights the complexity of glucocorticoid treatment in patients with chronic lung disease and a role for AMs in susceptibility to secondary infection and exacerbation.…”
Section: Macrophage Mediation Of Airway Diseasementioning
confidence: 99%
“…Furthermore, removal of dead/dying cells by AMs results in subsequent impaired phagocytosis and bacterial killing and impaired clearance of S. pneumoniae. 24 Moreover, it has been shown that administration of glucocorticoids during active murine pneumonia infection further hinders the ability of AMs to kill bacteria via inhibition of cytokine production 25. This highlights the complexity of glucocorticoid treatment in patients with chronic lung disease and a role for AMs in susceptibility to secondary infection and exacerbation.…”
Section: Macrophage Mediation Of Airway Diseasementioning
confidence: 99%
“…Decreased macrophage trafficking in infants results in delayed clearance of pneumococcal colonization (9). Reducing the bactericidal function of alveolar macrophages with glucocorticoid leads to inhibition of pulmonary pneumococcal clearance in mice (10), while promoting CCL2-mediated macrophage recruitment with macrolides accelerates clearance of nasopharyngeal pneumococcal colonization in mice (11). Although the significance of macrophages in clearance of pneumococci has been well established, the related molecular mechanisms remain poorly understood.…”
mentioning
confidence: 99%
“…GC/GR signaling enhances the efferocytic properties of macrophages (Giles et al, 2001;Heasman et al, 2003;Stolberg et al, 2015), for instance, by increasing the expression of Mertk or Anxa1 as a core aspect of their anti-inflammatory effects (Koenen et al, 2018;Yona and Gordon, 2007;Zizzo et al, 2012). Efferocytosis is associated with macrophage polarization state since it induces the acquisition of an anti-inflammatory/resolving phenotype (Fadok et al, 1998;Han et al, 2016;Huynh et al, 2002;Zhang et al, 2019a), thus provides a bridge in macrophage function across sterile and LPS induced inflammation.…”
Section: Discussionmentioning
confidence: 99%